EFFECT OF SILVER NANOPARTICLE-MEDIATED WOUND THERAPY ON BIOCHEMICAL, HEMATOLOGICAL, AND HISTOLOGICAL PARAMETERS - Chauhan, Pallavi Singh; Shrivastava, Vikas; Gbks, Prasad; Tomar, Rajesh Singh (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Green synthesis of nanoparticles has been used as an alternative, efficient, less expensive, and ecofriendly method. Ancient approaches employed for nanoparticle fabrication were chemical and physical methods having various disadvantages as they are costly and potentially harmful to the environment, use of harsh chemicals and stringent protocol for synthesizing nanoparticles. The present study is focused on the synthesis of silver nanoparticles by bio-availed as well as chemical route and evaluation of their wound healing potential in Wistar rat model. Methods: Extraction of Syzygium cumini was done and was used for silver nanoparticle synthesis. The synthesized nanoparticles were characterized by ultraviolet-visible spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, and transmission electron microscopy, which confirms the availability of nanosilver particles with marginally spherical morphology. The particles were then carried forward for treating impaired diabetic wounds in Wistar rat models. Regular photography was done and wound healing parameters were monitored throughout the study along with analyzing other parameters such as biochemical, hematological, and histological parameters. Results: The study showed that the sizes of the synthesized nanoparticles are below 100 nm. The results obtained from in vivo studies showed efficient wound healing potential of silver nanoparticles as compared to pre-existing drug povidone-iodine, i.e., the percentage reduction in wound area after therapy is 96.09% in case of biosynthesized silver nanoparticle-treated group, 97.7% reduction in chemically synthesized silver nanoparticle-treated group, 64.28% reduction in case of pre-existing drug povidone-iodine-treated group, 37.5% reduction in case of diabetic control group (diabetic), and 97.5% reduction in normal control group (non-diabetic). Results showed that biosynthesized silver nanoparticles showed less toxicity with respect to liver and kidney functions. Skin histology results showed increased sign of wound healing in biosynthesized silver nanoparticles. Hematology results showed no such variation. Conclusion: The study will help to synthesize new economically viable potential biosynthesized nanoparticles along with providing the approach to develop the medication at nanoscale level.